Development of high-repetition-rate X-ray chopper system for time-resolved measurements with synchrotron radiation. (28th February 2017) - Osawa, Hitoshi; Kudo, Togo; Kimura, Shigeru
Abstract: A high-repetition-rate X-ray chopper system has been developed for pump–probe time-resolved measurements with synchrotron radiation. This system has a rotating disc with 108 or 54 grooves (X-ray path on the disc) that provides an opening time of 1.17 or 0.52 µs with a rotating speed of 28, 997 rpm. Also, this system could select single-pulse X-rays every 4 or 8 periods of the several-bunch structure operated at SPring-8, corresponding to an X-ray pulse frequency of 52.2 or 26.1 kHz, respectively, and is suitable for pump–probe studies of electronic devices such as next-generation memory devices.